State Construction and National Education Policy in Congo from 1911 to 1997: Contributing to Policy Analysis in Sub-Saharan Africa - (:unkn) unknown (My University, 2007)
Political science has traditionally focused on issues pertaining to the study of regimes, political elites, institutions and power, discriminating against analyses of the “day to day” functioning of the State, that is, what the State does or does not do. Yet a great number of scholars consider that political analysis should unfold within a more dynamic envisioning of the State-society relationship so as to foster the knowledge of the State while using new problematiques. This thesis attempts to understand the process of State construction in Congo not from a previous conventional perspective but rather from a thorough analysis of policy-oriented strategies of local political actors in the course of implementing the national education agenda. It aims at showing capacities often used by those actors in creating legal rational mechanisms sustaining State modernization via realistic public policies, how they operate in selecting those policies, which are alternatives offered to them, issues arisen and resources mobilized in the course of implementation, and how they impact the process of State construction. Sequencing and interactionist approaches are useful in understanding various educational programs set against the backdrop of State construction from 1911 (when schooling was officially instituted) to 1997 (at the outbreak of the second Congolese civil war). Historical sociology further contributes to a comprehensive look at the constitution of the Congolese political field.
Keywords: African Research